Political humor: Analysis of political caricature in the referendum 2007 - Vega Umaña, Lhiam (2012)
The present article analyzes the political caricature, published on the cover of Semanario Universidad, during the referendum process developed in Costa Rica in 2007. The study exposes what is the role played by the political caricature, in the Costa Rican political system, during that juncture with respect to the Free Trade Agreement between Central America, Dominican Republic and the United States. (DR-CAFTA)